2011
DOI: 10.1055/s-0030-1270962
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Cucurbitacins fromWilbrandia ebracteataCogn.

Abstract: Chemical investigation of the roots of Wilbrandia ebracteata Cogn. (Cucurbitaceae) led to the isolation of two new (1- 2) and four known (3- 6) cucurbitacins. Their structures were elucidated by NMR and MS and compared with related compounds. The in vitro cytotoxicity of isolated compounds was evaluated against RD, KB, HCT-8, and A549 cell lines showing strong activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Recently, we described novel cytotoxic cucurbitacins isolated from Wilbrandia ebracteata Cogn. [ 21 ] and unraveled the apoptotic mechanism in NSCLC cells for the most active compound [ 27 ]. We also described new semisynthetic derivatives of cucurbitacin B that are highly cytotoxic against A549 cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we described novel cytotoxic cucurbitacins isolated from Wilbrandia ebracteata Cogn. [ 21 ] and unraveled the apoptotic mechanism in NSCLC cells for the most active compound [ 27 ]. We also described new semisynthetic derivatives of cucurbitacin B that are highly cytotoxic against A549 cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1 (dihydrocucurbitacin B), 3 (cucurbitacin R), 4 (25-deacetyl-dihydrocucurbitacin B), 5 (cayaponoside A), and 6 (dihydrocucurbitacin B-2- O -glucoside) were isolated from the roots of Wilbrandia ebracteata Cogn. (Cucurbitaceae), as previously described. , Compound 2 (cucurbitacin B) was isolated from the fruits of Luffa operculata (L.) Cogn. (Cucurbitaceae) .…”
Section: Methodsmentioning
confidence: 99%
“…(Cucurbitaceae), as previously described. 29,30 Compound 2 (cucurbitacin B) was isolated from the fruits of Luffa operculata (L.) Cogn. (Cucurbitaceae).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cucurbitacin B is one of the most abundant and widely studied members of this group. , Recently, a novel cucurbitacin B semisynthetic derivative (DACE) (Figure ) was investigated by our research group and showed potent antiproliferative activity against nonsmall cell lung cancer in vitro and in vivo a mouse model of lung cancer . Other cucurbitacins with potential antiproliferative effects have also been described by our research group. As described by Silva et al, DACE presents advantages from the chemical synthesis perspective when compared with the precursor cucurbitacin B. The semisynthesis process is simple, short, and might represent a new route to generate new anticancer compounds.…”
Section: Introductionmentioning
confidence: 99%